Neoadjuvant Chemotherapy Versus Direct Surgery for Locally Advanced Gastric Cancer With Serosal Invasion (cT4NxM0): A Propensity Score-Matched Analysis - Xu, Wei; Wang, Lingquan; Yan, Chao; He, Changyu; Lu, Sheng; Ni, Zhentian; Hua, Zichen; Zhu, Zhenglun; Sah, Birendra Kumar; Yang, Zhongyin; Zheng, Yanan; Feng, Runhua; et al. (Frontiers in Oncology, 2021)
Background: For locally advanced gastric cancer (LAGC) with serosal invasion (cT4NxM0), adjuvant chemotherapy (AC) after D2 gastrectomy is the standard therapy in Asia. However, perioperative chemotherapy (PCT) combined with D2 gastrectomy is mostly suggested in Europe and America. As a part of PCT, the value of neoadjuvant chemotherapy (NAC) is unclear. We investigated whether NAC could further improve survival and other outcomes for these patients. Methods: Patients with cT4NxM0 gastric cancer who underwent D2 gastrectomy were analyzed. The patients were divided into two groups based on whether they received NAC: the neoadjuvant chemotherapy (NAC) and direct surgery (S) groups. After propensity score matching (1:1 ratio), survival and perioperative outcomes were analyzed between the two groups. Results: A total of 902 patients met all the eligibility criteria and were enrolled. After propensity score matching, 221 matched pairs of patients were identified. The median overall survival (OS) and disease-free survival (DFS) of all patients were 75.10 and 43.67 months, respectively. The median OS of patients in the NAC and S groups were undefined and 29.80 months, respectively (P<0.0001). The median DFS of patients in the NAC and S groups were undefined and 22.60 months (P<0.0001). There were no significant differences in the radical degrees of operation between the two groups (P=0.07). However, there were significant differences in postoperative hospital stay (P<0.001) and complications (P=0.037) between the two groups. Conclusion: This study suggested NAC can further improve prognosis and prevent recurrence in LAGC (cT4NxM0) patients. NAC is feasible and safe for LAGC (cT4NxM0) patients, and does not increase the risk of perioperative surgery.